1999
DOI: 10.1016/s0895-7061(98)00209-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of single-drug therapy for the cardiac effects of hypertension

Abstract: Much has been learned in epidemiologic studies and clinical trials about the relationships between hypertension and cardiac anatomic and functional responses, as well as the effects of antihypertensive treatment on those responses. The results of recent multicenter trials have supported initial concerns that not all drugs effective for blood pressure reduction are effective for reduction of LV mass and regression of LVH. However, recent trials of single-drug therapy suggest that those agents initially believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…[170] Nonetheless, echocardiographic evaluation of the ejection phase indices of left ventricular function showed that antihypertensive treatment leading to LVM reduction is not associated with decreases in systolic function. This could be especially severe in sudden increases of blood pressure because the left ventricle is no longer protected against overload by compensatory hypertrophy.…”
Section: Effects On Systolic Functionmentioning
confidence: 98%
“…[170] Nonetheless, echocardiographic evaluation of the ejection phase indices of left ventricular function showed that antihypertensive treatment leading to LVM reduction is not associated with decreases in systolic function. This could be especially severe in sudden increases of blood pressure because the left ventricle is no longer protected against overload by compensatory hypertrophy.…”
Section: Effects On Systolic Functionmentioning
confidence: 98%
“…Due to favorable effects, such as reduction of blood pressure, regression of ventricular hypertrophy, increase of the ischemic threshold, these drugs can be used in diastolic heart failure, especially in the presence of hypertension or coronary artery disease and atrial or ventricular arrhythmias. 13) Theoretically, it should be also beneficial in patients with exertional dyspnea by blunting heart rate response to exertion. However, their use in patients with advanced diastolic dysfunction (grade III or IV) must be done with great caution.…”
Section: Beta-blockersmentioning
confidence: 99%
“…This class of medication is especially useful in treating patients with underlying coronary artery disease and those with atrial or ventricular arrhythmia [31]. …”
Section: Beta-blockersmentioning
confidence: 99%